Technical efficiency of health-care systems in selected middle-income countries: An empirical investigation - Heba Nassar; Hala Sakr; Asmaa Mohamed Ezzat; Pakinam Fikry (Review of Economics and Political Science (REPS), 2020)
Purpose This paper aims to evaluate the technical efficiency of the health-care systems in 21 selected middle-income countries during the period (2000-2017) and determine the source of inefficiency whether it is transient (short run) or persistent (long run). Design/methodology/approach The study uses the stochastic frontier analysis technique through employing the generalized true random effects model which overcomes the drawbacks of the previously introduced stochastic frontier models and allows for the separation between unobserved heterogeneity, persistent inefficiency and transient inefficiency. Findings Persistent efficiency is lower than the transient efficiency; hence, there are more efficiency gains that can be made by the selected countries by adopting long-term policies that aim at reforming the structure of the health-care system in the less efficient countries such as South Africa and Russia. The most efficient countries are Vietnam, Mexico and China which adopted a social health insurance that covers almost the whole population with the aim of increasing access to health-care services. Also, decentralization in health-care has assisted in adopting health-care policies that are suitable for both the rural and urban areas based on their specific conditions and health-care needs. A key success in the implementation of the adopted long-term policies by those countries is the continuous monitoring and evaluation of their outcomes and comparing them with the predefined targets and conducting any necessary modifications to ensure their movement in the right path to achieve their goals. Originality/value Although several studies have evaluated the technical efficiency both across and within countries using non-parametric (data envelopment analysis) and parametric (stochastic frontier analysis) approaches, to the best of the authors' knowledge, this is the first attempt to evaluate the technical efficiency of selected middle-income countries during the period (2000-2017) using the generalized true random effects stochastic frontier analysis model.
Keywords: 330; Health-care systems; Middle-income countries; Persistent efficiency; Stochastic frontier analysis; Technical efficiency; Transient efficiency